Surgical Affections in Calves at Dhunot and Bogura Sadar Upazilas (Journal of the Bangladesh Agricultural University, 2020)
The study aimed to provide baseline information about various surgical affections of calves at Dhunot and Bogura Sadar Upazila Veterinary Hospitals in Bogura District from January 2014 to December 2018. Various surgical affections were diagnosed in 233 calves, this constituted 10.76% of the total surgical cases (2165) admitted during that period at two Upazila. The surgical affections recorded in calves along with occurrence rate were umbilical hernia (9.01%), atresia ani (4.72%), myiasis (8.15%), abscesses (24.03%), omphalitis (25.32%), dermoid cyst (1.72%), fracture (15.88%), and knuckling of limbs (11.16%). Most surgical affections occurred at birth or within 6 weeks of birth. The acquired surgical affections (73.39%) recorded in calves were omphalitis, abscess, fracture and myiasis, and the congenital surgical affections (26.61%) were umbilical hernia, atresia ani, dermoid cyst and knuckling of limbs of the overall surgical cases. In conclusion, omphalitis, abscess, and fracture were found to be the three major surgical affections in calves, but proper surgical management may cure most of the ailments.J Bangladesh Agril Univ 18(3): 623–628, 2020https://doi.org/10.5455/JBAU.99392